Hydroxybutyl chitosan/ oxidized glucomannan self-healing hydrogels as BMSCs-derived exosomes carriers for advanced stretchable wounds. (March 2022) - Qin, Di; Zhang, Andi; Wang, Na; Yao, Yingxia; Chen, Xiguang; Liu, Ya
Highlights: Exomes loaded self-healing hydrogels (exo⊂EOH1) was prepared via Schiff base reaction. exo⊂EOH1 promotes cell migration and reduce exosomes leakage under destruction. exo⊂EOH1 significantly enhances stretchable full-thickness skin wound healing. Abstract: Skin wounds, especially full-thickness skin wounds on stretchable sites, including areas elbows, knees, and nape, usually undergo delayed or poor healing due to the frequent movements. Self-healing hydrogels are ideal candidates for wound dressings by automatically repairing the gel structural defects and restoring its function to solve the rapid degradation and leakage of loading materials caused by limb compression or movement. In this study, self-healing hydrogels loaded with biological exosome nanoparticles derived from bone mesenchymal stem cells was successfully constructed using hydroxybutyl chitosan and oxidized konjac glucomannan via reversible Schiff base reaction. Due to its three-dimensional porous structure and self-healing properties, hydrogels performed well in G′ recover under 350% strain, promoting cell migration and reducing the exosomes leakage by 30.4% and 42.4% at 14 h and 16 h when hydrogel network destroyed compared with hydroxybutyl chitosan hydrogels, respectively. In addition, hydrogels also exhibited antibacterial properties against E. coli and S. aureus contributed by the ε -poly- l -lysine coating. In vivo, exosome-loaded self-healing hydrogels significantly enhanced the stretchable wounds healing in full-thickness skin defects model by facilitating angiogenesis, promoting collagen deposition and helping skin remodeling. The results suggest that the novel multifunctional exosomes-loaded hydrogels as an advanced wound dressings exhibited great potential for tissue remodeling and regeneration on stretchable wounds. Abstract : Image, graphical abstract .